Molecular analysis of cyenopyrafen resistance in the two‐spotted spider mite Tetranychus urticae. Issue 1 (10th August 2015) - Khalighi, Mousaalreza; Dermauw, Wannes; Wybouw, Nicky; Bajda, Sabina; Osakabe, Masahiro; Tirry, Luc; Van Leeuwen, Thomas
Abstract: BACKGROUND: Cyenopyrafen is a recently developed acaricide with a new mode of action as a complex II inhibitor. However, it was recently shown that cross‐resistance to cyenopyrafen can occur in resistant field strains of Tetranychus urticae, which might be linked to the previous use of classical METI acaricides. Here, we selected for cyenopyrafen resistance and studied the molecular mechanisms that underlie resistance. RESULTS: Selection for cyenopyrafen resistance confers cross‐resistance to the complex II inhibitor cyflumetofen, but also to pyridaben, a frequently used complex I inhibitor. Cyenopyrafen resistance is highly synergised by piperonyl butoxide, and a 15‐fold higher P450 activity was detected in the resistant strain. Target‐site resistance was not detected. Genome‐wide gene expression data, followed by a meta‐analysis of previously obtained gene expression data, revealed the overexpression specifically of CYP392A11 and CYP392A12 . CONCLUSIONS: Cyenopyrafen resistance is strongly linked to the overexpression of two P450s, which probably explains the observed cross‐resistance. This information is highly valuable, as the novel complex II inhibitors cyenopyrafen and cyflumetofen are in the process of worldwide registration. The role of both CYP392A11 and CYP392A12 should be further supported by functional expression, but they are very promising candidates as molecular diagnostic markers for monitoring cyenopyrafen susceptibility in the field. © 2015 Society of Chemical Industry